Police GPS Surveillance on Vehicles and the Warrant Requirement: “For a While I’ve Been Watching You Steady” - Hughes, Tom “Tad” (American journal of criminal justice, 2013)
The global positioning system (GPS) has become ubiquitous to modern American life. The system supplies direction for travel through navigation systems as well as employee monitoring capabilities (Rosenberg Washington Journal of Law, Technology, and Arts 6:143–154, 2010 ). Law Enforcement has also found GPS to be a valuable tool. The technology provides a relatively cheap and highly effective way to monitor a suspect’s movement. Depending on the device, travel data can be reported in real time or be retrieved from the implanted device at intervals (Shah Journal of Law, Technology, and Policy 2009:281–294, 2009 ). This paper will first explore the core foundational Fourth Amendment cases that shape the use of GPS devices by law enforcement. Next, the federal circuits and state supreme courts’ decisions that have addressed the use of GPS will be reviewed. Third, the case of U.S. v. Jones ( 2012 ), which was recently decided by the United States Supreme Court, will be examined. Last, the policy implications of the current legal landscape regarding the use of GPS by police will be discussed.